2020
DOI: 10.1101/2020.11.26.400028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How to best evaluate applications for junior fellowships? Remote evaluation and face-to-face panel meetings compared

Abstract: ObjectivesTo test a simplified evaluation of fellowship proposals by analyzing the agreement of funding decisions with the official evaluation, and to examine the use of a lottery-based decision for proposals of similar quality.DesignThe study involved 134 junior fellowship proposals (Postdoc.Mobility). The official method used two panel reviewers who independently scored the application, followed by triage and discussion of selected applications in a panel. Very competitive/uncompetitive proposals were direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Of note, in the context of the Explorer Grant scheme of the New Zealand Health Research Council, Liu et al (2020) recently reported that most applicants agreed with random selection. So far, the SNSF received no negative or positive reactions to the use of random selection from applicants (Bieri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, in the context of the Explorer Grant scheme of the New Zealand Health Research Council, Liu et al (2020) recently reported that most applicants agreed with random selection. So far, the SNSF received no negative or positive reactions to the use of random selection from applicants (Bieri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Health Research Council of New Zealand (Liu et al, 2020), the Volkswagen Foundation (2017) and recently the Austrian Research Fund (2020) are funders that have applied lotteries, with a focus on transformative research or unconventional research ideas. The SNSF introduced a modified lottery for its junior fellowship scheme, focusing on proposals near the funding line (Adam, 2019;Bieri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%